Effects of Interval Time of the Epley Maneuver on Immediate Reduction of Positional Nystagmus: A Randomized, Controlled, Non-blinded Clinical Trial - Imai, Takao; Okumura, Tomoko; Sato, Takashi; Takeda, Noriaki; Ohta, Yumi; Okazaki, Suzuyo; Inohara, Hidenori (Frontiers in Neurology, 2019)
Objective: The Epley maneuver (EM) has an immediate effect: rapid reduction of positional nystagmus. Benign paroxysmal positional vertigo (BPPV) causes BPPV fatigue, which constitutes fatigability of positional nystagmus and vertigo with repeated performance of the Dix-Hallpike test; notably, BPPV fatigability becomes ineffective over time. We hypothesized that the immediate effect of the EM is caused by BPPV fatigue. Therefore, we suspected that performance of the EM with intervals between head positions would worsen the immediate reduction of positional nystagmus in patients with BPPV, because BPPV fatigability would become ineffective during performance of this therapy. Methods: Forty patients with newly diagnosed BPPV were randomly assigned to the following two groups; one group performed the EM without intervals between positions (group A), and the other group performed the EM with 3-minute intervals between positions (group B). The primary outcome measure was the ratio of maximum slow-phase eye velocity (MSPEV) of positional nystagmus soon after the EM, compared with that measured before the EM. Secondary outcome included whether a 30-minute interval after the EM enabled recovery of MSPEV of positional nystagmus to the original value. This study followed the CONSORT 2010 reporting standards. Results: In both groups A and B, the immediate effect of the EM could be observed, because MSPEV during the second Dix-Hallpike test was significantly smaller than MSPEV during the first Dix-Hallpike test (p<0.0001 in group A, p<0.0001 in group B). The primary outcome measure was larger in group B than in group A (p=0.0029). The immediate effect faded 30 minutes later (secondary outcome). Conclusions: This study showed that the EM had an immediate effect both with and without interval time in each head position of the EM. Because setting interval time in each head position of the EM reduced the immediate effect of the EM, interval time during the EM adds less benefit. This finding can reduce the effort exerted by doctors, as well as the discomfort experienced by patients with pc-BPPV, during EM. However, this immediate effect may be caused by BPPV fatigue, and may fade rapidly. Classification of Evidence: 1b